Localities of plants collected by Thomas Baines on the Baines-Chapman expedition to Lake Ngami and Victoria Falls 1861 – 1863. Issue 4 (December 2016) - Goyder, David
Summary An annotated itinerary of Thomas Baines' travels during the Baines-Chapman expedition from Walvis Bay to Lake Ngami and the Victoria Falls is presented, with comments on plants encountered. Conflicts with the often cryptic label data found on Baines' specimens are discussed. A gazetteer of significant localities along the route is also included.